Gender Dynamics in Roles, Resources, Control, Decision Making and Household Welfare in Ghana: Implications for Agricultural Sustainability - Amoako, Prince Kwadwo; Ayerakwa, Margaret Frimpong; Tham-Agyekum, Dr Enoch Kwame (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This study investigates the gender dynamics in cocoa farming households across the Ashanti and Western South regions, focusing on their implications for agricultural sustainability. Using a cross-sectional survey design, data were collected from 401 cocoa farmers through structured questionnaires. Data was analysed using descriptive (frequency, percentage) and inferential statistics (independent samples t-test). Results indicate that men dominate physically demanding tasks such as land preparation (82.8%) and pesticide application (85.0%). In comparison, women are more involved in less intensive tasks like drying cocoa beans (33.2%) and reproductive roles such as food preparation (74.6%). Men control essential resources, including land (82.3%), capital (78.6%), and agricultural tools, while women have greater control over processing resources like drying mats (20.4%). Decision-making is similarly male-dominated, with men leading in areas like farming inputs (82.0%) and household security (85.5%), although women exert influence in daily food decisions (42.4%). Despite these disparities, no significant gender-based differences were found in outcomes for yield, income, or food security. The study highlights the need for gender-inclusive policies and targeted interventions to promote equitable access to resources, enhance women's decision-making capacity, and encourage their involvement in sustainable cocoa farming.